A study of correlation between Cholelithiasis and Fatty liver from ultrasonography of patients in Vajira Hospital - Molee, Patamaporn; Kuisakorn, Wanisacha; Laosuksanttiwong, Yanutta; Kerdpon, Natchaya; Pirom, Manaya (Journal of Associated Medical Sciences, 2025)
Background: The rising consumption of Western-style fast food—high in carbohydrates, sugar, and fat—together with a fast-paced lifestyle, occupational stress, and physical inactivity, represents a major risk factor for fatty liver disease, which can progress to hepatitis, cirrhosis, or hepatocellular carcinoma. Evidence linking fatty liver and cholelithiasis is growing globally, yet data from Thailand and Southeast Asia remain scarce, despite both conditions being increasingly prevalent. Cholelithiasis, a common gastrointestinal disorder affecting 5–10% of the Thai population, particularly females and older adults, may also be associated with fatty liver disease. Objectives: This study investigated the correlation between cholelithiasis and fatty liver disease using ultrasonographic data from patients at Vajira Hospital, aiming to address this regional knowledge gap and inform preventive strategies. Materials and methods: A retrospective analysis was performed on 311 patients aged ≥50 years who underwent upper abdominal ultrasonography at Vajira Hospital between 2023 and 2024. Collected data included gender, age, gallstone size, and diagnostic findings. Patients were classified into two groups: 132 with cholelithiasis and 179 without. Statistical analyses included descriptive statistics (mean, SD, frequency, percentage) and inferential tests (t-test, chi-square test, and logistic regression). Results: Of the 311 patients, 162 (52.1%) had fatty liver, with a mean age of 62±8.46 years; 62.3% were female and 37.7% were male. Among these, 73 patients (45.1%) had concurrent cholelithiasis (66% female, 34% male), with a mean gallstone size of 1.09±0.53 cm. The remaining 89 patients (54.9%) had fatty liver disease without cholelithiasis (60% female, 40% male). A significant inverse association was observed between age and fatty liver disease (p=0.003), indicating that younger patients within this ≥50-year cohort were more likely to be affected. Conclusion: Cholelithiasis was not significantly associated with fatty liver disease. However, fatty liver showed a novel inverse correlation with age, with higher prevalence among younger adults within the ≥50-year cohort. This finding, which contrasts with previous reports of increasing prevalence with age, may reflect methodological factors and lifestyle influences in Thailand’s urban population. These results emphasize the need for early screening and targeted public health interventions for working-age adults, while acknowledging limitations related to study design, absence of key confounders, and restricted age range.